Force statistics and correlations in dense granular packings - Müller, Micha-Klaus; Luding, Stefan; Pöschel, Thorsten (Chemical Physics, 2010)
In dense, static, polydisperse granular media under isotropic pressure, the probability density and the correlations of particle-wall contact forces are studied. Furthermore, the probability density functions of the populations of pressures measured with different sized circular pressure cells are examined. The questions answered are: (i) What is the number of contacts that has to be considered so that the measured pressure lies within a certain error margin from its expectation value? (ii) What is the statistics of the pressure probability density as function of the size of the pressure cell? Astonishing non-random correlations between contact forces are evidenced that lead to a rapid decay of the width of the distribution and range at least 10-15 particle diameters. Finally, an experiment is proposed to tackle and better understand this issue. © 2010 Elsevier B.V. All rights reserved.
Keywords: DEM simulations; Dense static granular packings; Force and stress correlations; Pressure cells